Pengaruh Stres, Motivasi, dan Kecerdasan Spritual Terhadap Prestasi Belajar pada Mahasiswa Jurusan Sistem Informasi STIKOM Dinamika Bangsa Jambi - Eddy Suratno (Universitas Batanghari, 2020)
The purpose of this research is to provide scientific evidence whether there is an influence of stress, motivation, and Spritual intelligence towards learning achievement in students of information system of STIKOM dynamics of the Nation Jambi. The population of this research is the student information system of STIKOM Dinamika Bangsa Jambi, which has passed the study period of one year and has not programmed a thesis. Sampling techniques using purposive sampling. Research Data is obtained from questionnaires (primary). This study was conducted using multiple linear regression analyses as a model of analysis. From the results of the study showed that stress variables have no effect on the student learning achievement of information systems, while the variable motivation, and spiritual intelligence significantly affect the student learning achievement of information systems. Variable stress, motivation, and spiritual intelligence are able to explain the achievement of learning in Student information system of STIKOM dynamics of the nation of Jambi, the rest are dijelaksan by other factors that are not researched.